2016
DOI: 10.1002/ptr.5737
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resveratrol Supplementation on Blood Glucose, Insulin, Insulin Resistance, Triglyceride, and Periodontal Markers in Type 2 Diabetic Patients with Chronic Periodontitis

Abstract: The aim of this study was to investigate the impact of resveratrol supplementation along with non-surgical periodontal treatment on blood glucose, insulin, insulin resistance, triglyceride (TG), and periodontal markers in patients with type 2 diabetes with periodontal disease. In this double-blind clinical trial study, 43 patients with diabetes with chronic periodontitis were participated. Subjects were randomly allocated to intervention and control groups. The intervention and control groups received either 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 54 publications
2
64
1
1
Order By: Relevance
“…In a study conducted by Elliott et al, fasting insulin and HbA1c were unchanged following 5 g/d resveratrol supplementation (Elliott et al, 2009). There is also another study showing a significant effect of resveratrol on HOMA-IR improvement without significant change on FBS (Zare Javid et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study conducted by Elliott et al, fasting insulin and HbA1c were unchanged following 5 g/d resveratrol supplementation (Elliott et al, 2009). There is also another study showing a significant effect of resveratrol on HOMA-IR improvement without significant change on FBS (Zare Javid et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Although, some studies reached nonsignificant results (Bashmakov et al, 2014;Goh et al, 2014;Timmers et al, 2016). A randomized controlled trial showed no significant effect of 30-day resveratrol treatment on hepatic and peripheral insulin sensitivity (Timmers et al, 2016), while two other studies reported significant beneficial effect on insulin resistance following resveratrol supplementation (Movahed et al, 2013;Zare Javid et al, 2017). Contradictory results prompted us to perform a randomized controlled trial to investigate if resveratrol supplementation affects glycemic control, lipid profile, and body composition in overweight patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a human clinical trial reported by Zare Javid et al . suggested that resveratrol supplementation may be beneficial as adjuvant therapy along with nonsurgical periodontal treatment in insulin resistance and improving the periodontal status in patients with diabetes and periodontal disease …”
Section: Treatment Of Periodontitits With Resveratrol and Its Derivativementioning
confidence: 93%
“…Resveratrol is therefore proposed to manage comorbidity or multimorbidity in the elderly. For example, in T2DM patients with chronic periodontitis, resveratrol significantly reduced insulin and insulin resistance while improving the periodontal status with an insignificant effect on the fasting blood glucose and triglycerides levels . At least 25% of diabetic patients suffer from foot ulcers, which can become chronic and severe .…”
Section: Completed Clinical Trialsmentioning
confidence: 99%